Isolation of Lodderomyces elongisporus from the Catheter Tip of a Fungemia Patient in the Middle East - Suhail Ahmad; Zia U. Khan; Molly Johny; Najat M. Ashour; Wehad H. Al-Tourah; Leena Joseph; Rachel Chandy (Case Reports in Medicine, 2013)
Lodderomyces elongisporus is phenotypically closely related to Candida parapsilosis and has recently been identified as an infrequent cause of bloodstream infections in patients from Asia and Mexico. We report here the isolation of Lodderomyces elongisporus from the catheter of a suspected case of fungemia. The identity of the isolate was confirmed by phenotypic characteristics and ribosomal DNA sequencing.